A CONCEPTUAL STUDY ON DEVELOPING SUPPLEMENTARY SPEAKING MATERIALS FOR TERTIARY-LEVEL EFL STUDENTS USING THE ADDIE MODEL - Lutpiyah Lutpiyah; Nasywa Kamilah; Selnistia Hidayani (PT. Intelek Cendikiawan Nusantara, 2025)
This study aims to develop supplementary speaking materials for tertiary-level EFL students using the ADDIE model. The development was intended to support speaking instruction and provide additional materials for students’ speaking practice. This research used a research and development approach that followed the five stages of the ADDIE model: analysis, design, development, implementation, and evaluation. The data were collected through needs analysis, expert judgment, and students’ feedback on the developed materials. The findings showed that the supplementary speaking materials were appropriate and useful for supporting students’ speaking activities. The materials were considered relevant to students’ needs and suitable for use in tertiary-level EFL classes. In conclusion, the supplementary speaking materials developed through the ADDIE model can be used as additional learning resources to support speaking instruction for tertiary-level EFL students